Synthesis and proton conduction properties of lanthanide amino-sulfophosphonates - Cabeza-Díaz, Aurelio; Bazaga-García, Montse; Pérez-Colodrero, Rosario Mercedes; Salcedo, Inés R.; Villemin, Didier; Olivera-Pastor, Pascual; Losilla, Enrique R. (My University, 2016)
Crystalline acid-functionalized metal phosphonates are potential candidates as proton conducting electrolytes. Their frameworks can be chemically modified to contain proton carriers such as acidic groups (P-OH; -SO3H, -COOH,…) and guest molecules (H2O, NH3,…) that generates hydrogen bond networks stable in a wide range of temperature [1,2]. In this work, focus is laid on properties derived from the combination of lanthanide ions with the amino-sulfophosphonate ligand (H2O3PCH2)2-N-(CH2)2-SO3H. Hightrough-put screening was followed to reach the optimal synthesis conditions under solvothermal conditions at 140 ºC. Isolated polycrystalline solids, Ln[(O3PCH2)2-NH-(CH2)2-SO3H].2H2O (Ln= La, Pr and Sm), crystallize in the monoclinic (La) and orthorhombic (Pr and Sm) systems with unit cell volume of ~2548 Å3. Preliminary proton conductivity measurements for Sm derivative have been carried out between 25º and 80 ºC at relative humidity (RH) values of 70 % and 95 %. The sample exhibits enhanced conductivity at high RH and T (Figure 1) and constant activation energies of 0.4 eV, typical of a Grothuss mechanism of proton.
Keywords: Polímeros; Polymers; phosphonates; metal organic frameworks; polymers synthesis; Coordination Polymers